Fungal diversity in speleothem surfaces, bat guano, dead arthropods, and cavern water of limestone caves in Sabah, Borneo - Ibrahem Ghani Wasti (2020)
Borneo is a global biodiversity hotspot. However, its limestone caves are one of its least-studied ecosystems. In this study, we report for the first time the fungal species richness, diversity, and abundance from four caves in Sabah, Borneo: Balambangan cave, Gomantong cave, Madai cave, and Keruak cave. These caves are categorized as being anthropogenically active or non-active caves. Gomantong cave and Madai cave are considered anthropogenically active because of their high visitation rate, swiftlet farming and nest harvesting, and relatively higher land-use in the area surrounding their forest reserves. We sampled four different known fungal substrates from inside the cave environment, e.g. speleothem (n = 20), cavern water (n = 14), bat guano (n = 11), and dead arthropods (n = 9). Opportunistic sampling was utilized, and the dilution method was performed during isolation of fungi. Potato Dextrose Agar (PDA) and Malt Extract Agar (MEA) were used for isolation of pure isolates of fungi. In total, 180 pure fungal isolates were produced from all samples collected. Morphological characterization and molecular analysis of the Internal Transcribed Spacer (ITS) gene region were utilized for identification. A total of 56 operational taxonomic units (OTU) were identified from BLASTn and phylogenetic analyses of the 90 new fungal gene sequences. Overall, 75 morphological taxonomic units (MTU) from 35 genera, 11 orders, and two divisions were identified. Fifty-eight taxa were successfully identified to the species level and the remaining 17 to the genus level. Division Ascomycota (96.1%) dominated the composition of fungal isolated, followed by Basidiomycota (3.9%). Madai cave had the highest average fungal abundance per sample for speleothem (299.3 CFU/cm2), cavern water (335.0 CFU/ml), and bat guano (6,266.7 CFU/g). Only Gomantong cave yielded dead arthropod samples. Active caves showed consistently higher fungal species occurrence and abundance compared to non-active caves. Speleothem fungal abundance in active caves was statistically significantly higher than non-active caves. Average fungal species occurrence was slightly higher for active caves but not statistically significant. Speleothem and bat guano showed higher diversity indices than cavern water, but this is dependent on the ecology of the individual caves. Distance from the cave entrance is considered a plausible factor affecting cave mycoflora as five out of 18 linear regression analyses were statistically significant. Eurotiales and Hypocreales fungi dominated fungal composition, due to their cosmopolitan and entomopathogenic nature, respectively. Arthropods, bats, and humans likely play a significant role in fungal introductions, fungal dispersal, and nutrient availability in cave ecosystems. The findings of this study provide baseline data on cave fungi and sheds light on their ecological relationships. Future mycological studies in caves should utilize culture-independent methods of isolation and identification to eliminate bias on fast-growing fungi.